Desenvolvimento e estudo de estabilidade de formulações cosméticas contendo extrato de Stryphnodendron adstringens (Mart.) Coville e Centella asiatica (L.) Urb. com atividade antioxidante (Revista Brasileira Multidisciplinar, 2023)
Phytocosmetics are defined as cosmetic formulations that contain plant actives in their composition, as well as the ancient people used to include plant species in their daily lives, but beyond its usuais applications, as meals or medication. The request for this category of product has been increasing over the years, because of the demand for healthcare products and considering that the natural actives are good for people’s health. In this context, Brazil is one of the main raw material providers, since it’s home of a great biodiversity, which can encourage researches, including the development of phytocosmetics. Among the plants found in the country, many are registered in the Brazilian Pharmacopoeia, whose actions and applications are known not only by the people, but recognized by the experts, including Stryphnodendron adstringens (Mart.) Coville and Centella asiatica (L.) Urb.’s antioxidant action. Therefore, the present study had as objectives manipulating gel and cream formulations, in which the actives S. adstringens and C. asiatica were incorporated, and  perform stability tests on the prepared formulations. The results obtained indicate stable formulations, in which the concentrations related to the Efficiency Concentration (EC50) of the antioxidant action of the extracts, determined in another study, were incorporated.